Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and secondary battery

By loading nanosilicon on a porous carbon matrix containing F elements and optimizing the preparation method, the pressure resistance and polarization problems of silicon carbon materials in lithium-ion batteries are solved, and higher energy density and cycling stability are achieved.

CN119864392AActive Publication Date: 2025-04-22ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411860954.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-22
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing silicon carbon materials have poor pressure resistance and large material polarization in lithium-ion batteries, resulting in low energy density.

Method used

Fast lithium-ion conductor LiF is generated to optimize the stability of the SEI film by loading nanosilicon on a porous carbon matrix containing F elements and enhancing the material's pressure resistance and polarization reduction by specific preparation methods.

Benefits of technology

The pressure resistance and circulation performance of silicon carbon negative electrode materials are improved, the ultimate pressure density of the material is increased, the polarization is reduced, and the energy density and circulation stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193188340000121
    Figure BDA0005193188340000121
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and relates to a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode plate and a secondary battery, the silicon-carbon negative electrode material comprises a porous carbon matrix and nanometer silicon loaded on the porous carbon matrix, and the porous carbon matrix contains an F element; the limiting compaction density of the silicon-carbon negative electrode material is S g / cm < 3 >, the true density of the silicon-carbon negative electrode material is Z g / cm < 3 >, S * Z is larger than or equal to 2.3 and smaller than or equal to 3.2, and the value range of S is 1.05-1.27. Nano silicon is loaded on a porous carbon matrix containing an F element, so that the pressure resistance of the material is enhanced, the limit compaction of the material is higher than that of a non-crosslinked material, and the true density of the material is also higher than that of conventional silicon carbon. The ultimate compaction of the material is large, the ultimate compaction difference between the material and graphite is reduced, the structural stability is good, and meanwhile the compatibility between the material and electrolyte is improved. The method comprises the following steps: cross-linking a resin carbon source and polyol fluoride to enhance the cross-linking degree of the carbon source; and the obtained porous carbon matrix is high in hardness, compression strength and breaking strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode sheet and a secondary battery. Background Art

[0002] With the rapid development of new energy vehicles, higher requirements are placed on the performance of vehicle power batteries. Research and development of high-rate charging and discharging performance and high safety power lithium-ion batteries has become one of the main solutions for vehicle power supply.

[0003] Currently, the most mature commercial lithium-ion battery negative electrode material is artificial graphite, with a reversible specific capacity of about 340mAh / g-360mAh / g. However, graphite materials have poor structural stability and poor compatibility with electrolytes. In addition, the anisotropic structural characteristics of graphite limit the free diffusion of lithium ions in the graphite structure, thereby affecting the rate performance of graphite negative electrode materials. Silicon-carbon materials have once again attracted attention in power lithium-ion batteries due to their good rate performance and cycle performance.

[0004] However, the existing technology has fatal flaws. On the one hand, silicon-carbon materials have poor pressure resistance. The difference in the ultimate compactness of the two is too large. In the process of mixing silicon-carbon with graphite, silicon-carbon is more easily broken, resulting in a sharp deterioration in the cycle life and expansion of the battery cell, and even causing the battery cell cycle to dive. If the design compactness is reduced, the energy density of the battery cell will be greatly reduced, which will lack competitiveness in practical applications. On the other hand, due to the poor intrinsic ionic conductivity of silicon-carbon materials, the material polarization is large, and the large polarization leads to low material capacity, resulting in low energy density of the battery cell. Summary of the invention

[0005] The purpose of the present invention is to provide a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode sheet and a secondary battery in view of the deficiencies of the prior art, redesign the silicon-carbon material, increase its compaction density, improve its pressure resistance, and introduce F atoms to generate a fast lithium ion conductor LiF when forming a SEI film, thereby reducing material polarization. The generated LiF makes the SEI more stable and optimizes the composition and structure of the SEI, thereby improving the material capacity, first effect, and long cycle performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A silicon-carbon negative electrode material, comprising a porous carbon matrix and nano-silicon loaded on the porous carbon matrix, wherein the porous carbon matrix contains F element;

[0008] The ultimate compaction density of the silicon-carbon negative electrode material is S g / cm 3 The true density of the silicon-carbon negative electrode material is Zg / cm3 , 2.3≤S*Z≤3.2, and the value range of S is 1.05-1.27.

[0009] Preferably, the silicon-carbon negative electrode material further comprises a carbon coating layer coating at least a portion of the surface of the porous carbon matrix.

[0010] Preferably, the particle size Dv50 of the porous carbon matrix is ​​5-10 μm; and / or the particle size of the nano-silicon is 6-10 nanometers; and / or the mass of the nano-silicon is 46%-48% of the mass of the porous carbon matrix.

[0011] The present invention also provides a method for preparing the above silicon-carbon negative electrode material, comprising the following steps:

[0012] Step 1, mixing a resin carbon source and a polyol fluoride, and heating them in a constant temperature water bath to obtain a carbon source substrate;

[0013] Step 2, carbonizing, forming pores and purifying the carbon source substrate to obtain a porous carbon matrix;

[0014] Step 3, introducing a silane mixed gas into the porous carbon matrix to vapor-deposit silicon to obtain a nano-silicon-porous carbon material;

[0015] Step 4: introducing a mixed gas containing a protective gas and an organic gas source into the nano-silicon-porous carbon material to perform chemical vapor deposition, and carbon-coating the nano-silicon-porous carbon material to obtain a silicon-carbon negative electrode material.

[0016] Preferably, in step 1, the constant temperature water bath heating comprises heating in a constant temperature water bath at 50-100° C. for 1-4 hours while stirring.

[0017] Preferably, the ratio of the mass of the polyol fluoride to the total mass of the polyol fluoride and the resin carbon source is 5%-30%.

[0018] Preferably, the ratio of the mass of the polyol fluoride to the total mass of the polyol fluoride and the resin carbon source is 10%-25%.

[0019] Preferably, the resinous carbon source comprises one or more of phenolic resin and epoxy resin.

[0020] Preferably, the polyol fluoride includes one or more of fluorinated glycerol, fluorinated xylitol, fluorinated sorbitol, fluorinated ethylene glycol, fluorinated 1,2-propylene glycol, fluorinated 1,4-butanediol, fluorinated 1,6-hexanediol, fluorinated neopentyl glycol, fluorinated diethylene glycol, fluorinated dipropylene glycol, and fluorinated trimethylolpropane.

[0021] Preferably, in step 2, the carbonization includes carbonizing at 900-1200°C for 3-6 hours in an inert atmosphere; and / or, the pore-forming includes mixing the carbon matrix with the pore-forming agent and calcining at 850-1000°C for 1-2 hours; and / or, the purification includes acid washing and water washing the calcined product to neutrality, and then calcining at 500-600°C for 3-4 hours.

[0022] Furthermore, the pore former is an alkaline pore former; preferably, the pore former includes at least one of sodium hydroxide and potassium hydroxide; preferably, the concentration of the pore former is 1-2 mol / L; preferably, the addition amount of the pore former is 8%-15% of the mass of the carbon matrix.

[0023] Furthermore, the pore volume of the carbon source substrate treated with the pore forming agent is 0.6-10 cm 3 / g, the pore distribution structure is micropores accounting for 80%-90%, mesopores accounting for 5%-19%, and macropores accounting for 1%-5%, among which, the pore size of micropores is ≤2nm, the pore size of mesopores is 2-50nm, and the pore size of macropores is ≥50nm.

[0024] Preferably, in step 3, the vapor-deposited silicon includes placing a porous carbon substrate in a reaction device, introducing a first mixed gas containing a first protective gas and a silicon source gas, and vapor-depositing silicon on the porous carbon substrate; preferably, the conditions for the vapor-deposited silicon are deposition at 350-450°C for 1-3h; preferably, the content of the first protective gas is 10%-30% of the volume of the first mixed gas; preferably, the silicon source gas includes silane gas; preferably, the first protective gas includes at least one of helium, nitrogen, argon and krypton.

[0025] Preferably, in step 4, the organic gas source includes at least one of acetylene, ethylene, and methane, and the protective gas includes at least one of nitrogen and argon; and / or, in step 4, the deposition temperature is 500-700°C, the deposition time is 1-3 hours, and the soft carbon deposition amount is 10%-15% of the mass of the silicon-carbon negative electrode material.

[0026] A negative electrode sheet comprises the above-mentioned silicon-carbon negative electrode material.

[0027] A secondary battery comprises the negative electrode sheet mentioned above.

[0028] Compared with the prior art, the beneficial effects of the present invention are:

[0029] By loading nano-silicon on a porous carbon matrix containing F elements, the pressure resistance of the material is enhanced, and the ultimate pressure resistance of the obtained material is as high as 1.27g / cm 3 , higher than 1.0g / cm2 of the uncrosslinked material 3, and the true density of the material is 2.2-2.5g / cm 3 , greater than 2.0g / cm of conventional silicon carbon 3 . This material has a large ultimate compression density. Compared with existing silicon-carbon materials, it has a smaller ultimate compression density difference with graphite, has better structural stability, and improves compatibility with electrolytes. The resin carbon source is cross-linked with polyol fluoride to enhance the degree of cross-linking of the carbon source; the resulting porous carbon matrix has high hardness, compressive strength and flexural strength. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] According to a first aspect of the present invention, the present invention provides a silicon-carbon negative electrode material, comprising a porous carbon matrix and nano-silicon supported on the porous carbon matrix, wherein the porous carbon matrix contains F element;

[0032] The ultimate compaction density of the silicon-carbon negative electrode material is S g / cm 3 , the true density of silicon-carbon negative electrode material is Zg / cm 3 , 2.3≤S*Z≤3.2, the value range of S is 1.05-1.27. Specifically, the ultimate compaction density of the silicon-carbon negative electrode material is 1.1g / cm 3 , 1.12g / cm 3 , 1.14g / cm 3 , 1.15g / cm 3 , 1.18g / cm 3 , 1.2g / cm 3 , 1.22g / cm 3 , 1.25g / cm 3 and 1.27 g / cm 3 wait.

[0033] In one embodiment of the present invention, the silicon-carbon negative electrode material further includes a carbon coating layer coating at least a portion of the surface of the porous carbon matrix.

[0034] In one embodiment of the present invention, the particle size Dv50 of the porous carbon matrix is ​​5-10 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc.

[0035] According to the second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned silicon-carbon negative electrode material, comprising the following steps:

[0036] Step 1, mixing a resin carbon source and a polyol fluoride, and heating them in a constant temperature water bath to obtain a carbon source substrate;

[0037] Step 2, carbonizing, forming pores and purifying the carbon source substrate to obtain a porous carbon matrix;

[0038] Step 3, introducing a silane mixed gas into the porous carbon matrix to vapor-deposit silicon to obtain a nano-silicon-porous carbon material;

[0039] Step 4: introducing a mixed gas containing a protective gas and an organic gas source into the nano-silicon-porous carbon material to perform chemical vapor deposition, and carbon-coating the nano-silicon-porous carbon material to obtain a silicon-carbon negative electrode material.

[0040] In one embodiment of the present invention, in step 1, the constant temperature water bath heating includes heating in a constant temperature water bath at 50-100° C. for 1-4 hours while stirring. The temperature of the constant temperature water bath can be, for example, 50° C., 60° C., 70° C., 75° C., 80° C., 90° C. or 100° C., etc. The heating time can also be 1 hour, 2 hours, 3 hours or 4 hours, etc.

[0041] In one embodiment of the present invention, the mass ratio of the polyol fluoride to the total mass of the polyol fluoride and the resin carbon source is 5%-30%. More preferably, the mass ratio of the polyol fluoride to the total mass of the polyol fluoride and the resin carbon source is 10%-25%, for example, 10%, 12%, 15%, 17% or 20%, etc.

[0042] In one embodiment of the present invention, the resin carbon source includes one or more of phenolic resin and epoxy resin, and the polyol fluoride includes one or more of fluorinated glycerol, fluorinated xylitol, fluorinated sorbitol, fluorinated ethylene glycol, fluorinated 1,2-propylene glycol, fluorinated 1,4-butanediol, fluorinated 1,6-hexanediol, fluorinated neopentyl glycol, fluorinated diethylene glycol, fluorinated dipropylene glycol, and fluorinated trimethylolpropane. By cross-linking the polyol fluoride with the resin carbon source, the cross-linking degree of the carbon source is enhanced, and the pressure resistance of the sintered material is enhanced, and the ultimate compression density of the obtained material can reach 1.27g / cm 3 , true density is 2.2-2.5g / cm 3 .

[0043] In one embodiment according to the present invention, in step 2, the carbonization includes carbonizing at 900-1200°C for 3-6 hours in an inert atmosphere. Too low a temperature cannot carbonize better, and there are too many heteroatoms, such as oxygen atoms, resulting in a low first efficiency of the material. Too high a carbonization temperature results in a loose structure of the obtained carbon source and poor structural stability, resulting in poor pressure resistance of the material. Too short a time cannot carbonize better, and there are too many heteroatoms, such as oxygen atoms, resulting in a low first efficiency of the material. Too long a time results in a loose structure of the obtained carbon source and poor structural stability, resulting in poor pressure resistance of the material. Therefore, carbonization is carried out under higher temperature and longer time conditions, while reducing heteroatoms and enhancing the stability of the formed carbon structure, ensuring the optimal combination of structural stability and first efficiency of the material. If the temperature is too high and the time is too short, the gasification reaction will be violent during carbonization, and the obtained carbon matrix will be loose and not pressure-resistant. The inert gas that can be used in this embodiment is a nitrogen atmosphere, etc., to isolate the oxygen in the air and protect the carbon source substrate.

[0044] In one embodiment of the present invention, the pore-forming comprises mixing the carbon matrix with a pore-forming agent, calcining at 850-1000°C for 1-2 hours; and / or, the purification comprises acid-washing and water-washing the calcined product to neutrality, and then calcining at 500-600°C for 3-4 hours. The pore-forming agent is an alkaline pore-forming agent; preferably, the pore-forming agent comprises at least one of sodium hydroxide and potassium hydroxide; preferably, the concentration of the pore-forming agent is 1-2 mol / L; preferably, the amount of the pore-forming agent added is 8%-15% of the mass of the carbon matrix.

[0045] In one embodiment of the present invention, the pore volume of the carbon source substrate treated with the pore forming agent is 0.6-10 cm 3 / g, the pore distribution structure is that micropores account for 80%-90%, mesopores account for 5%-19%, and macropores account for 1%-5%. Among them, the pore size of micropores is ≤2nm, the pore size of mesopores is 2-50nm, and the pore size of macropores is ≥50nm.

[0046] If the concentration and amount of pore-forming agent are too small or the etching time is too short, the pore distribution of the material will be uneven, the porosity will be low, and most of the pores will be micropores. If the concentration and amount of alkali are too large or the etching time is too long, most of the pores will be mesopores or even macropores, and the structure will be looser and the pressure resistance will be poor. Increasing the pore volume will increase the proportion of mesopores and reduce the proportion of micropores.

[0047] If the purification time is too short, the content of heteroatoms will be high, and if it is too long, the porous carbon structure will be unstable. The carbon source substrate is further purified by high-temperature heating to reduce the content of heteroatoms, especially oxygen atoms (<2%), and improve the initial efficiency of the material in battery applications.

[0048] The particle size range Dv50 of the porous carbon matrix is ​​5-10μm. If it is too small, the yield is low and the cost is increased. If it is too large, the diffusion impedance of lithium ions in the particles is large and the rate performance is poor. If the particle size is too large, Dv100 is larger than the roller gap size of the coating machine, scratches may occur during coating and the electrode yield is low.

[0049] In one embodiment of the present invention, the vapor deposited silicon includes placing a porous carbon substrate in a reaction device, introducing a first mixed gas containing a first protective gas and a silicon source gas, and vapor depositing silicon on the porous carbon substrate; preferably, the conditions for the vapor deposition of silicon are deposition at 350-450°C for 1-3h; preferably, the content of the first protective gas is 10%-30% of the volume of the first mixed gas; preferably, the silicon source gas includes silane gas; preferably, the first protective gas includes at least one of helium, nitrogen, argon and krypton.

[0050] If the deposition temperature is too low, silane will be difficult to reduce and the production capacity will be low; if the deposition temperature is too high, nano-silicon will be converted from amorphous silicon to crystalline silicon, resulting in expansion anisotropy and increasing the expansion rate of the material; and if the deposition temperature is too high, chemically inert silicon carbide will be easily generated.

[0051] The deposition time can be 1 hour, 2 hours or 3 hours, etc. If the time is too short, silicon cannot be completely deposited inside. If the time is too long, silicon is easy to accumulate on the surface, increasing the expansion of the material and shortening the service life. If the size of the deposited nano-silicon particles is too small, there will be more interfaces between silicon and carbon, more lithium ion transfer interfaces, greater impedance, and greater polarization of the material during use. If the size of the nano-silicon is too large, the uniformity of lithium embedding inside the silicon will be worse, it will be easier to break, and the expansion will increase.

[0052] In one embodiment of the present invention, the silane mixed gas is introduced into the porous carbon matrix and reduced to nano-silicon, and the nano-silicon grows in the porous carbon matrix to obtain nano-silicon-porous carbon material; the particle size of the nano-silicon is 6-10 nanometers, and the deposition amount of the nano-silicon is 46%-48%. The particle size of the nano-silicon can be 6 nanometers, 7 nanometers, 8 nanometers, 9 nanometers or 10 nanometers, and the deposition amount of the nano-silicon is 46%, 47% or 48%, and the like. Too low results in low initial efficiency of the material, low cathode gram capacity, and increased cost of the battery cell. Too high material expansion is large, the stress is large during expansion, and the damage to the porous carbon matrix is ​​serious. The material is more likely to pulverize and fail.

[0053] In one embodiment of the present invention, in step 4, the organic gas source includes at least one of acetylene, ethylene, and methane, and the protective gas includes at least one of nitrogen and argon; and / or, in step 4, the deposition temperature is 500-700°C, the deposition time is 1-3 hours, and the soft carbon deposition amount is 10%-15% of the mass of the silicon-carbon negative electrode material. If the deposition temperature is too high, chemically inert silicon carbide is easily generated, and if the deposition temperature is too low, the organic gas source is difficult to be reduced. The same applies to deposition time that is too long or too short. Too much deposition leads to low initial efficiency of the material and increased lithium ion diffusion impedance; too little material has a large specific surface area, resulting in low initial efficiency, and a large contact area with water during homogenization, which is easy to produce gas. The speed of the gas flow is reduced, the speed at which the organic gas is reduced to carbon is reduced, and the pores in the porous carbon are slowly deposited to enhance the protection of silicon in the porous carbon and the expansion inhibition during lithium insertion. Finally, a silicon-based negative electrode composite material with a large pore volume, a large proportion of mesopores and blocked pores is obtained.

[0054] According to the third aspect of the present invention, the present invention further provides a negative electrode sheet, comprising the above-mentioned silicon-carbon negative electrode material.

[0055] According to a fourth aspect of the present invention, the present invention further provides a secondary battery comprising the above-mentioned negative electrode sheet.

[0056] The present invention will be further described below with reference to specific embodiments.

[0057] Embodiment 1:

[0058] A method for preparing a silicon-carbon negative electrode material is as follows:

[0059] Step 1: Cross-linking of phenolic resin

[0060] A phenolic resin and fluorinated glycerol were mixed, where the phenolic resin was phenol-formaldehyde resin (purchased from Shaoguan Derui Chemical Industry Co., Ltd., CAS: 9003-35-4), and heated in a constant temperature water bath at 50°C for 1 hour with stirring. The mass of fluorinated glycerol accounted for 5% of the total mass of the phenolic resin and fluorinated glycerol, to obtain a carbon source substrate.

[0061] Step 2: Preparation of porous carbon substrate

[0062] Carbonization: First, the carbon source substrate in step 1 is carbonized. The carbonization conditions of the carbon source substrate are as follows: a carbonization temperature of 950° C., a carbonization time of 3 hours, and nitrogen is introduced for high-temperature carbonization to isolate oxygen in the air and protect the carbon source substrate.

[0063] Activated pore formation: The above-mentioned carbon source substrate was mixed with the pore-forming agent, placed in a constant temperature device at 850°C, and etched for 1 hour. After the reaction was completed, it was acid-washed, washed with water until neutral, dried, calcined at 500°C for 4 hours, and crushed to obtain a porous carbon matrix; the pore volume of the porous carbon matrix was 0.7 cm 3 / g, Dv50 is 8.5μm, and in the pore distribution of the porous carbon matrix, micropores (pore diameter <2nm) account for 90%, mesopores (2-50nm) account for 5%, and macropores (pore diameter >50nm) account for 5%; the pore-forming agent is potassium hydroxide with a concentration of 0.6mol / L, and the amount of the pore-forming agent added is 8% of the mass of the carbon source substrate.

[0064] Step 3: Silane deposition

[0065] The porous carbon matrix obtained in step 2 is placed in a rotary furnace, and a silane mixed gas consisting of protective gas nitrogen and silane gas is introduced for deposition, wherein the volume proportion of the protective gas is 15%. The rotary furnace used has a capacity of 50 kg, a deposition temperature of 400°C, a deposition time of 3 hours, and a silicon deposition amount of 48%, thereby obtaining a nano-silicon-porous carbon material.

[0066] Step 4: Carbon Packing

[0067] The product obtained in step 3 is placed in a rotary kiln / fluidized bed, and chemical vapor deposition is carried out in a mixed atmosphere of protective gas nitrogen and organic gas source acetylene to perform soft carbon coating on the nano-silicon-porous carbon material. During this process, the deposition temperature is 600°C, the deposition time is 2 hours, and the soft carbon deposition amount is 10% of the mass of the silicon-carbon negative electrode material.

[0068] Embodiment 2:

[0069] The only difference from Example 1 is that in step 1, the mixture is heated in a 50°C constant temperature water bath while being stirred for 1 hour. The mass of fluorinated glycerol accounts for 10% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as in Example 1.

[0070] Embodiment 3:

[0071] The only difference from Example 1 is that in step 1, the mixture is heated in a 50°C constant temperature water bath while being stirred for 1 hour. The mass of fluorinated glycerol accounts for 15% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as in Example 1.

[0072] Embodiment 4:

[0073] The only difference from Example 1 is that in step 1, the mixture is heated in a 50°C constant temperature water bath while being stirred for 2 hours. The mass of fluorinated glycerol accounts for 10% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as in Example 1.

[0074] Embodiment 5:

[0075] The only difference from Example 1 is that in step 1, the mixture is heated in a 75°C constant temperature water bath while being stirred for 2 hours. The mass of fluorinated glycerol accounts for 10% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as in Example 1.

[0076] Embodiment 6:

[0077] The only difference from Example 1 is that in step 1, the mixture is heated in a constant temperature water bath at 100° C. for 2 hours while being stirred. The mass of fluorinated glycerol accounts for 10% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as those in Example 1.

[0078] Embodiment 7:

[0079] The only difference from Example 1 is that in step 1, the mixture is heated in a 50°C constant temperature water bath while being stirred for 3 hours. The mass of fluorinated glycerol accounts for 10% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as in Example 1.

[0080] Embodiment 8:

[0081] The only difference from Example 1 is that the phenolic resin is replaced by an equal amount of bisphenol A epoxy resin (purchased from Langfang Rongkun Environmental Protection Technology Co., Ltd., model: epoxy resin E128), and the rest is consistent with Example 1.

[0082] Embodiment 9:

[0083] The only difference from Example 1 is that fluorinated glycerol is replaced by an equal amount of fluorinated ethylene glycol, and the rest is the same as Example 1.

[0084] Embodiment 10:

[0085] The only difference from Example 1 is that the fluorinated glycerol is replaced by an equal amount of fluorinated xylitol, and the rest is the same as Example 1.

[0086] Embodiment 11:

[0087] The only difference from Example 1 is that in step 1, the mixture is heated in a 50°C constant temperature water bath while being stirred for 1 hour. The mass of fluorinated glycerol accounts for 20% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as in Example 1.

[0088] Embodiment 12:

[0089] The only difference from Example 1 is that in step 1, the mixture is heated in a 50°C constant temperature water bath while being stirred for 1 hour. The mass of fluorinated glycerol accounts for 25% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as in Example 1.

[0090] Embodiment 13:

[0091] The only difference from Example 1 is that in step 1, the mixture is heated in a 50°C constant temperature water bath while being stirred for 1 hour. The mass of fluorinated glycerol accounts for 30% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as in Example 1.

[0092] Comparative Example 1:

[0093] The only difference from Example 1 is that: in Comparative Example 1, no polyol fluoride is added, but the same phenolic resin as in Example 1 is directly used to prepare the porous carbon substrate, and the rest is consistent with Example 1.

[0094] Comparative Example 2:

[0095] The only difference from Example 1 is that in step 1, the mixture is heated in a 50°C constant temperature water bath while being stirred for 1 hour. The mass of fluorinated glycerol accounts for 2% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as in Example 1.

[0096] Comparative Example 3:

[0097] The only difference from Example 1 is that in step 1, the mixture is heated in a 50°C constant temperature water bath while being stirred for 1 hour. The mass of fluorinated glycerol accounts for 35% of the total mass of the phenolic resin and fluorinated glycerol. Steps 2, 3, and 4 are the same as in Example 1.

[0098] The negative electrode materials of the above embodiments and comparative examples are further applied to the preparation of lithium ion batteries, and the specific preparation method includes:

[0099] S1. Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride in a mass ratio of 97:1.5:1.5, add N-methylpyrrolidone (NMP), and stir evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%. The positive electrode slurry is evenly coated on one surface of an aluminum foil with a thickness of 8μm, and the aluminum foil is dried at 125°C for 1h to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Then, after cold pressing, cutting, and slitting, dry under vacuum conditions at 125°C for 2h to obtain a positive electrode with a specification of 65mm×860mm.

[0100] S2. Preparation of negative electrode sheet: negative electrode material, CMC, PAA and CNT are mixed in a mass ratio of negative electrode material: CMC: PAA: CNT = 80:9:10:1, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 60wt%. The negative electrode slurry is evenly coated on one surface of a copper foil with a thickness of 6μm, and the copper foil is dried at 120°C to obtain a negative electrode coated with a negative electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a negative electrode coated with a negative electrode material layer on both sides. Then, after cold pressing, cutting and slitting, it is dried under vacuum conditions at 120°C for 2h to obtain a negative electrode with a specification of 69mm×868mm.

[0101] S3. Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, EC, PC and DMC are mixed in a mass ratio of 3:2:4 to obtain an organic solvent, and then lithium hexafluorophosphate is added to the organic solvent to obtain an electrolyte, wherein the concentration of the lithium salt is 1 mol / L.

[0102] S4. Assembly of lithium-ion battery: stack the positive electrode, separator (PE), and negative electrode prepared above in order, with the separator placed between the positive electrode and the negative electrode to play a role of isolation, and wind to obtain an electrode assembly. Assemble the electrode assembly into a button battery.

[0103] Performance tests, including ultimate compression, true density, capacity, first efficiency and cycle performance.

[0104] The test methods and conditions are as follows: (1) The ultimate compaction is the compaction of the electrode under a pressure of 60T; (2) The true density is calculated by the gas volume method, using the Archimedean principle, by measuring the change in gas volume after the sample is placed in the test chamber to calculate the true volume of the sample; (3) The capacity and first effect test steps are 0.1C discharge to 0.05V, let it stand for 5 minutes, 0.01C discharge to 0.05V let it stand for 5 minutes, 0.1C charge to 1.5V, let it stand for 5 minutes. (4) Cyclic capacity retention rate: 1C constant current and constant voltage charge to 4.53V, cut-off rate 0.05C, let it stand for 5 minutes; 1C constant current discharge to 3.0V, let it stand for 5 minutes. Cycle 800 times.

[0105] The specific test results are shown in Table 1.

[0106] Table 1:

[0107]

[0108]

[0109] According to the test results in Table 1, the silicon-carbon negative electrode material provided in the embodiment of the present invention not only contains F element, but also has a limiting compaction density of S g / cm 3 and true density is Z g / cm 3 It satisfies 2.3≤S*Z≤3.2, and the value range of S is 1.05-1.27, and has good electrochemical performance. Compared with comparative examples 1-3, its capacity, first efficiency and capacity retention rate are all higher.

[0110] After cross-linking the polyol fluoride of the present invention with a resin carbon source, the silicon-carbon negative electrode material with the above-mentioned suitable ultimate compaction density and true density can be obtained. The ultimate compaction density is much greater than the silicon-carbon material obtained without cross-linking using polyol fluoride, and its capacity and first efficiency are relatively improved, and the capacity retention rate is also improved.

[0111] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A silicon-carbon negative electrode material, characterized in that: It comprises a porous carbon matrix and nano-silicon supported on the porous carbon matrix, wherein the porous carbon matrix contains F element; The ultimate compaction density of the silicon-carbon negative electrode material is Sg / cm 3 The true density of the silicon-carbon negative electrode material is Z g / cm 3 , 2.3≤S*Z≤3.2, and the value range of S is 1.05-1.

27.

2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The silicon-carbon negative electrode material further includes a carbon coating layer coating at least a portion of the surface of the porous carbon matrix.

3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The particle size Dv50 of the porous carbon matrix is ​​5-10 μm; And / or, the particle size of the nano-silicon is 6-10 nanometers; And / or, the mass of the nano-silicon is 46%-48% of the mass of the porous carbon matrix.

4. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: Step 1, mixing a resin carbon source and a polyol fluoride, and heating them in a constant temperature water bath to obtain a carbon source substrate; Step 2, carbonizing, forming pores and purifying the carbon source substrate to obtain a porous carbon matrix; Step 3, introducing a silane mixed gas into the porous carbon matrix to vapor-deposit silicon to obtain a nano-silicon-porous carbon material; Step 4: introducing a mixed gas containing a protective gas and an organic gas source into the nano-silicon-porous carbon material to perform chemical vapor deposition, and carbon-coating the nano-silicon-porous carbon material to obtain a silicon-carbon negative electrode material.

5. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In step 1, the constant temperature water bath heating includes heating in a constant temperature water bath at 50-100° C. for 1-4 hours while stirring; And / or, the ratio of the mass of the polyol fluoride to the total mass of the polyol fluoride and the resin carbon source is 5%-30%; And / or, the ratio of the mass of the polyol fluoride to the total mass of the polyol fluoride and the resin carbon source is 10%-25%; And / or, the resinous carbon source comprises one or more of phenolic resin and epoxy resin; And / or, the polyol fluoride includes one or more of fluorinated glycerol, fluorinated xylitol, fluorinated sorbitol, fluorinated ethylene glycol, fluorinated 1,2-propylene glycol, fluorinated 1,4-butanediol, fluorinated 1,6-hexanediol, fluorinated neopentyl glycol, fluorinated diethylene glycol, fluorinated dipropylene glycol, and fluorinated trimethylolpropane.

6. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In step 2, the carbonization includes carbonizing at 900-1200° C. for 3-6 hours in an inert atmosphere; And / or, the pore forming comprises mixing the carbon matrix with a pore forming agent and calcining at 850-1000° C. for 1-2 hours; And / or, the purification includes acid washing and water washing the calcined product to neutrality, and then calcining at 500-600° C. for 3-4 hours; Preferably, the pore-forming agent is an alkaline pore-forming agent; Preferably, the pore-forming agent includes at least one of sodium hydroxide and potassium hydroxide; Preferably, the concentration of the pore-forming agent is 1-2 mol / L; Preferably, the amount of the pore-forming agent added is 8%-15% of the mass of the carbon matrix; Preferably, the pore volume of the carbon source substrate treated with the pore forming agent is 0.6-10 cm 3 / g, the pore distribution structure is micropores accounting for 80%-90%, mesopores accounting for 5%-19%, and macropores accounting for 1%-5%, among which, the pore size of micropores is ≤2nm, the pore size of mesopores is 2-50nm, and the pore size of macropores is ≥50nm.

7. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In step 3, the vapor deposition of silicon includes placing a porous carbon substrate in a reaction device, introducing a first mixed gas containing a first protective gas and a silicon source gas, and vapor-depositing silicon on the porous carbon substrate; Preferably, the vapor deposition of silicon is carried out at 350-450° C. for 1-3 hours; Preferably, the content of the first protective gas is 10%-30% of the volume of the first mixed gas; Preferably, the silicon source gas comprises silane gas; Preferably, the first protective gas includes at least one of helium, nitrogen, argon and krypton.

8. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In step 4, the organic gas source includes at least one of acetylene, ethylene, and methane, and the protective gas includes at least one of nitrogen and argon; And / or, in step 4, the deposition temperature is 500-700° C., the deposition time is 1-3 hours, and the soft carbon deposition amount is 10%-15% of the mass of the silicon-carbon negative electrode material.

9. A negative electrode sheet, characterized in that: It includes the silicon-carbon negative electrode material as described in any one of claims 1-3 or the silicon-carbon negative electrode material prepared by the preparation method of the silicon-carbon negative electrode material according to any one of claims 4-8.

10. A secondary battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Anode and secondary battery

    CN101320794A

  • Negative electrode material and preparation method thereof, electrochemical device and electronic device

    CN114051663A

  • Phenolic resin-based hard carbon material as well as preparation method and application thereof

    CN118108206A

  • Negative electrode material and preparation method thereof, electrochemical device and electronic device

    CN118630167A

  • Modified porous amorphous carbon negative electrode material as well as preparation method and application thereof

    CN118841546A